Pengembangan media pembelajaran berbasis Augmented Reality Infographic tentang Bandar Panarukan Abad XVIII-XIX untuk kelas XI IPS di SMAN 1 Suboh Kabupaten Situbondo - Jannah, Nurul; Wijaya, Daya Negri (Historiography: Journal of Indonesian History and Education, 2024)
Abstract In the modern era, technological developments in the field of education are increasingly rapid, especially those that occur in history learning which encourages the emergence of various learning innovations. The purpose of this research is to produce Augmented Reality Infographic learning media products in the historical material of the Colonial Port in Panarukan for class XI IPS students at SMAN 1 Suboh. The method applied in the research is the Borg and Gall model which consists of 10 steps. Then, based Borg & Gall, (1983) on can be simplified on a small scale into 6 steps, including: 1) Research and information gathering, 2) planning, 3) Initial product development, 4) initial field trial and validation stage, 5) product revision, and 6) main field trial. The results of the study showed that the material validation value obtained a percentage of 94.64% and for the results of media validation obtained a percentage of 98%. Then for the results of small group trials obtained a percentage of 90.28% a